Dose-Effectiveness Relationships Determining the Efficacy of Ibandronate for Management of Osteoporosis. Issue 26 (July 2015) - Hou, Yanjie; Gu, Ke; Xu, Chao; Ding, Huiyong; Liu, Changxin; Tuoheti, Yilihamu; Chebli., Caroline
<x xml:space="preserve">Abstract</x> Abstract The purpose of this study was to perform a meta-analysis on the efficacy of ibandronate by evaluating the effect sizes of different dosing regimens. Major electronic databases were searched from 1985 to February 2015. A random effects meta-analysis was performed in STATA. Data from 34 studies (13, 639 patients) were included in this meta-analysis. Ibandronate treatment significantly improved lumbar spine bone mineral density (BMD) as shown by the percent change from baseline (4.80%, P < 0.0001, 95% confidence interval [CI] [4.14, 5.45]). The respective effect sizes for oral intake and intravenous (IV) infusion were 4.57% and 5.22% (P < 0.0001, CIs [3.71, 5.42] and [4.37, 6.07]), respectively. All doses led to a significant increase in BMD except 2 oral dose regimens (1 mg/d: 4.65%, P = 0.285, 95% CI [−3.87, 13.18] and 0.5 mg/d: 3.60%, P = 0.38, 95% CI [−4.43, 11.64]. Ibandronate treatment (overall as well as dose wise) also significantly improved the total hip BMD—2.30% overall, 2.13% oral, and 2.63% IV (P < 0.0001, 95% CIs [1.96, 2.64], [1.70, 2.55], and [2.07, 3.20]), respectively. Ibandronate administration significantly decreased serum markers of bone resorption to −46.53% for C-terminal telopeptide of type 1 collagen, −24.03% for bone-specific alkaline phosphatase, and −50.17% for procollagen type I N-terminal propeptide (P < 0.0001, 95% CIs [−53.16, −39.91], [−31.28, −16.77], and [−64.13, −36.20]), respectively. Parathyroid hormone levels remained unaffected by ibandronate treatment (3.03%, P = 0.439, 95% CI [−5.06, 11.66]). There was no significant difference in the efficacy of ibandronate between oral or IV administration. Predominant dose regimens for IV administration were 1 to 3 mg/3 mo and 150 mg/mo oral and 2.5 mg/d for oral ibandronate treatment.